Attenuating Neurogenic Sympathetic Hyperreflexia Robustly Improves Antibacterial Immunity After Chronic Spinal Cord Injury - Mironets, Eugene (J Neurosci, 2020)
Spinal cord injury (SCI) disrupts critical physiological systems, including the cardiovascular and immune system. Plasticity of spinal circuits below the injury results in abnormal, heightened sympathetic responses, such as extreme, sudden hypertension that hallmarks life-threatening autonomic dysreflexia. Moreover, such sympathetic hyperreflexia detrimentally impacts other effector organs, including the spleen, resulting in spinal cord injury-induced immunodeficiency. Consequently, infection is a leading cause of mortality after SCI. Unfortunately, there are no current treatments that prophylactically limit sympathetic hyperreflexia to prevent subsequent effector organ dysfunction. The cytokine soluble tumor necrosis factor α (sTNFα) is upregulated in the CNS within minutes after SCI and remains elevated. Here, we report that commencing intrathecal administration of XPro1595, an inhibitor of sTNFα, at a clinically feasible, postinjury time point (i.e., 3 d after complete SCI) sufficiently diminishes maladaptive plasticity within the spinal sympathetic reflex circuit. This results in less severe autonomic dysreflexia, a real-time gauge of sympathetic hyperreflexia, for months postinjury. Remarkably, delayed delivery of the sTNFα inhibitor prevents sympathetic hyperreflexia-associated splenic atrophy and loss of leukocytes to dramatically improve the endogenous ability of chronic SCI rats to fight off pneumonia, a common cause of hospitalization after injury. The improved immune function with XPro1595 correlates with less noradrenergic fiber sprouting and normalized norepinephrine levels in the spleen, indicating that heightened, central sTNFα signaling drives peripheral, norepinephrine-mediated organ dysfunction, a novel mechanism of action. Thus, our preclinical study supports intrathecally targeting sTNFα as a viable strategy to broadly attenuate sympathetic dysregulation, thereby improving cardiovascular regulation and immunity long after SCI. SIGNIFICANCE STATEMENT Spinal cord injury (SCI) significantly disrupts immunity, thus increasing susceptibility to infection, a leading cause of morbidity in those living with SCI. Here, we report that commencing intrathecal administration of an inhibitor of the proinflammatory cytokine soluble tumor necrosis factor α days after an injury sufficiently diminishes autonomic dysreflexia, a real time gauge of sympathetic hyperreflexia, to prevent associated splenic atrophy. This dramatically improves the endogenous ability of chronically injured rats to fight off pneumonia, a common cause of hospitalization. This preclinical study could have a significant impact for broadly improving quality of life of SCI individuals.